Microwave-assisted Extraction for Maximizing the Yield of Phenolic Compounds and Antioxidant Capacity from Cacao Pod Husk (Theobroma cacao L.) - Nguyen, Van T.; Pham, Thi D.; Vu, Long B.; Nguyen, Van H.; Tran, Ngoc L. (Current Nutrition & Food Science, 2021)
Background: Extraction is an important step to obtain phytochemical compounds from natural materials. Among different extraction techniques, microwave-assisted extraction (MAE) is an advanced method with high extraction efficiency and low energy consumption. Objective: This study aimed to optimize the MAE parameters for obtaining the highest levels of phenolic compounds and antioxidant activity from cacao pod husk (CPH). Methods: The dried CPH was prepared using a microwave drying method. The CPH extract was prepared using a microwave-assisted extraction method. The powdered CPH extract was prepared using vacuum evaporation and freeze-drying methods. Phytochemical compounds and antioxidant capacity of CPH extracts were analyzed using spectrophotometric methods. Results: The optimal MAE parameters were 600 W microwave power, 5 s/min irradiation time, 30 min extraction time, and 50 mL/g solvent to sample ratio. Under these MAE parameters, total phenolic content (TPC), phenolic extraction efficiency (PEE), saponin content (SC), and DPPH radical scavenging capacity (DRSC) were achieved from the CPH to be 10.97 mg GAE/g dried sample, 76.82%, 70.10 mg EE/g dried sample, and 141.18 mg DPPH/g dried sample, respectively, which were not significantly different from the predicted values (10.38 mg GAE/g dried sample, 72.68%, 70.09 mg EE/g dried sample, and 121.49 mg DPPH/g dried sample, respectively). The residual moisture, water activity, density, water-soluble index and pH of powdered CPH extract were 9.72%, 0.38, 0.17 g/ml, 84.93% and 7.68, respectively. TPC, total flavonoid content (TFC) and SC of powdered CPH extract were 15.75 mg GAE/g dried sample, 27.03 mg CE/g dried sample and 133.67 mg EE/g dried sample, respectively. DRSC and ferric reducing antioxidant power (FRAP) of powdered CPH extract were 227.79 mg DPPH/g dried sample and 14.12 mg Fe(II)/g dried sample, respectively. Conclusion: The findings from this study reveal that the powdered extract obtained from the CPH at the optimal MAE parameters is a rich source of phytochemicals possessing great antioxidant activity. Therefore, it is a potential candidate to apply in functional foods.
Keywords: response surface methodology